Causal relationship between the two dimensions of self-directed humor and depression, anxiety, and subjective well-being: A longitudinal study. (October 2022) - Tsukawaki, Ryota; Imura, Tomoya; Hirakawa, Makoto
Abstract: The recently-developed Dual Self-Directed Humor Scale (DSDHS) is the first instrument for measuring individual differences between two dimensions of self-directed humor (SDH): negative (deleterious SDH) and positive (benign SDH). Thus far, the DSDHS has shown high validity and reliability. However, further validation of the underlying causal relationship between SDH and well-being is required. This study estimated the causal relationship between SDH and several well-being indicators via a two-wave, three-month interval, longitudinal dataset of college students ( N  = 453). A cross-lagged panel analysis showed that deleterious SDH predicted increased depression over time, while benign SDH predicted decreased depression and anxiety. There was also a two-way causal relationship, with anxiety decreasing benign SDH. These results enhance our understanding of the relationship between SDH and well-being. Highlights: This study collected longitudinal data on self-directed humor (SDH) and well-being. The analysis was performed via cross-lagged panel model. Deleterious self-directed humor predicted an increase in depression over time. Benign self-directed humor led to a decrease in depression and anxiety over time.